2018
DOI: 10.1101/273920
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attention and Emotion-Enhanced Memory: A Systematic Review and Meta-Analysis of Behavioural and Neuroimaging Evidence

Abstract: 7 8 ABSTRACT: The interaction between attention and emotion is posited to influence long-term 9 memory consolidation. We systematically reviewed experiments investigating the influence of 1 0 attention on emotional memory to determine: (i) the reported effect of attention on memory for 1 1 emotional stimuli, and (ii) whether there is homogeneity between behavioural and neuroimaging 1 2 based effects. Over half of the 47 included experiments found a moderate-to-large effect of attention 1 3 on emotional memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 102 publications
(189 reference statements)
0
7
0
Order By: Relevance
“…We also found better long-term memory discrimination for pleasant words than for the other semantic categories. Given the results from the lexical decision task, this indicates that prioritized processing during encoding for pleasant contents may have promoted deeper consolidation processes, which produced enhanced long-term memory performance (Weymar et al, 2012 ; for a review see Cross et al, 2018 ). As for the encoding data, previous research on recognition memory also found a memory advantage for pleasant words (Herbert et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found better long-term memory discrimination for pleasant words than for the other semantic categories. Given the results from the lexical decision task, this indicates that prioritized processing during encoding for pleasant contents may have promoted deeper consolidation processes, which produced enhanced long-term memory performance (Weymar et al, 2012 ; for a review see Cross et al, 2018 ). As for the encoding data, previous research on recognition memory also found a memory advantage for pleasant words (Herbert et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of studies specifically motivated by this goal is highlighted by a theme that has emerged through the discussion in this paper: Because of the relationship between attention and memory (attended stimuli are more likely to be remembered) and because many of the same factors affect both, much of what we currently know about the LPP is consistent with either function. This will likely continue to be the case unless we carefully design studies to distinguish these factors (and even then, will likely not be easy: see the appendix and Cross et al, 2018;Talmi, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…That is, the LPP could be associated with memory via cognitive factors, such as attention, that mediate the effect of emotion on memory in Talmi's (2013) model. However, the extent to which attention mediates the effects of emotional memory, even when memory is tested at a short delay, remains a matter of debate (Cross et al, 2018).…”
Section: The Lpp and Cognitive Factors Vs Tagging For Consolidationmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is less well remembered than is emotional content ( Kensinger, 2004 , 2007 ; Waring and Kensinger, 2009 , 2011 ; Talmi and McGarry, 2012 ; Chipchase and Chapman, 2013 ). The existence of attentional biases in favor of emotion provides a partial explanation for this trade-off ( Loftus et al, 1987 ; Steblay, 1992 ; Levine and Edelstein, 2009 ; Saunders, 2009 ; Schwabe et al, 2011 ; Fawcett et al, 2013 ; Cross et al, 2018 ), but the literature also mentions non-attentional factors ( Christianson et al, 1991 ; Riggs et al, 2011 ; Steinberger et al, 2011 ; Mickley Steinmetz and Kensinger, 2013 ; Mickley Steinmetz et al, 2014 ; An et al, 2020 ; Kensinger and Ford, 2020 ). The aim of our studies was to assess attentional and non-attentional effects of emotion in an immediate memory trade-off situation by controlling attentional processing with the use of “diffuse emotion” pictures during a patch-cued recognition paradigm.…”
Section: Discussionmentioning
confidence: 99%